Improvement Of Integrated Thematic Learning Outcomes With Contextual Teaching ApproachAnd Learning (CTL) In Class IV SDN 11 Aur Kuning - Yunela, Rada; Miaz, Yavelma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study is to improve students' integrated thematic learning outcomes using a contextual teaching and learning approach. Integrated thematic learning is one of learning that combines several subjects into one theme. integrated thematic learning also links learning with students' daily lives and integrated thematic learning can also make the learning process more meaningful, efficient and effective. This research method, using classroom action research methods. The research procedure is in the form of a cycle. Each cycle consists of three stages: planning, implementing actions, observing, and reflecting. Data collection technique through observation and test.This data collection uses instruments in the form of observation sheets of student and teacher observations in the learning process, then to find out the quality of student learning outcomes used evaluation sheets / tests. The results of the study indicate that the use of contextual teaching and learning approaches can improve student integrated thematic learning outcomes. From an average value of73.07 in the first cycle, to 85.15 in the second cycle